Affixation in the Script Song Lyric “A Little Piece of Heaven” - Eli Diana; Merry Rullyanti; Rhoma Shinta Simbolon (UNIVED Press, 2020)
The affixation is the important element of linguistic which interest to be analyzed. Almost in every book, newspaper, magazine, script, movie and songs lyric can found affixation. The objective of research is to know affixation in The Script song lyric. The main purpose of this research is to know how affixation process happens in The Script song lyric “A Little Piece of Heaven”. The method used in this research is descriptive qualitative method. The data used the text script of lyric. The result of this analysis shows that affixation process divided in two types depends on affixes itself. Keyword: Affixation, Lyric Song, A Little Piece of Heaven